Gender and the Greening of Buddhism: Exploring Scope for a Buddhist Ecofeminism in an Ultramodern Age - Tomalin, Emma (Journal for the Study of Religion, Nature and Culture, 2018)
Despite its popularity and appeal for many, ecofeminism has been criticized for essentializing and romanticizing women’s roles as close to nature, thereby reproducing colonialist and biologically determinist discourses that contribute to discrimination. In response there have been attempts to defend ecofeminism, arguing that such critiques are hyperbolic and that we need ecofeminism more than ever (Philips and Rumens 2016). In a climate of renewed interest in ecofeminism, I ask why is it that some faith traditions are represented to a far greater extent in ecofeminist literature than others? I pick up on this discrepancy within ecofeminism’s engagement between different religions through examining Buddhist responses to gender and ecology. In the article I adopt a theory of ultramodern Buddhism, developed by Halafoff and Rajkobal (2015), to understand Buddhism in the contemporary era. Three main research questions are addressed: (1) to what extent has ‘green Buddhism’ been gendered?; (2) why has there has been virtually no attempt to bring together feminist analysis with responses to Buddhism and environmentalism? Why have they been approached separately?; and (3) in what ways are Buddhist women (and men) combining gender analysis and environmentalism in practice in reference to or outside the framework of ecofeminism? To better understand why a Buddhist ecofeminism has not been named and claimed by Buddhists in either the West or Asia, there is a need for local-level empirical studies that examine subjective understandings of relationships between gender and environmentalism in the lives of ultramodern Buddhist practitioners rather than assuming a standard ecofeminist position as the primary reference point.